Painful and non-painful stimuli range as a base of context effect - Ivanec, Dragutin; Babić, Damir; Komljenović, Mario (2003)
In two separate experiments, the effect of stimulus context on ratings of perceived intensities induced by the electrocutaneous stimulation was investigated. The stimulus context was operationally defined as a range of stimuli used in one set of measurement (narrow-large). In the first experiment narrow stimuli range consisted of 5 electrocutaneous stimuli with intensities below the pain threshold. The large range, along with these 5 stimuli, included 5 more stimuli, painful in their intensity. The aim of this experiment was to investigate the ratings of stimulus intensity of those stimuli whose intensity was below the pain threshold in the narrow range series in comparison with these ratings in the series of both below and above the threshold level. The results show a significant difference of stimulus intensity assessments between two experimental conditions. In the condition with narrower range (when all the intensities are below pain threshold level) the intensity ratings are significantly higher then in the case of larger stimuli range. Second experiment tested the same context in relation to the ratings of the painful stimuli. A large stimuli range consisted of painful and non-painful stimuli, while narrow range consisted only of painful stimuli. This study showed no significant difference in the mean ratings level for painful stimuli regardless of the context of painful stimuli or the context of painful and non-painful stimuli. Both studies showed significant interaction of stimuli context and stimuli intensity. The largest differences between large and narrow stimuli range were found with more intensive (not-painful) stimuli, while second study showed marked differences of the two stimuli range with the least painful stimuli. These results confirm the importance of the stimuli context in perceived intensity of electrocutaneous stimulation. Variations in intensity ratings are smallest among the least intensive and the most intensive stimuli while mainly the intensity ratings of the mid-intensity stimuli is influenced by the stimuli context.
Projekt MZOS
ENG